PERKEMBANGAN FATWA MUI TENTANG MASALAH ZAKAT - Nopiardo, Widi (JURIS (Jurnal Ilmiah Syariah), 2017)
In the management of zakat, of there are parties that require regulations and need fatwa as a reference in the management of zakat. This type of research was normative research using qualitative analysis. The type of data in this research were secondary data which were taken from relevant books, internet media, documents, and previous research which studied about the farwa of about zakat. The data were analyzed by using qualitative data with method of analysis and normative study based on existing written sources. The results showed that from 1982 s.d. 2011 there were 10 fatwas discussing zakat that can be presented in detail as follow: 2 fatwas in 1982, 1 fatwa in 1996, 2 fatwas in 2003,1 fatwa in 2009,and 4 fatwasin 2011.